Physicochemical Properties and Antioxidant Activity of Multiflora Honey from Kerinci Regency, Jambi - Apriantini, Astari; Endrawati, Yuni Cahya; Yunia, Olin Aulia (Universitas Halu Oleo, 2022)
aim of this study was to examine the physicochemical properties and antioxidant activities of multifloral honey (Apis dorsata forest honey) and (Apis cerana cultivated honey) from Kerinci, Jambi. The analysis consist of the intensity of colour, pH, viscosity, water content, ash content, sugar content, HMF content, acidity and antioxidant activity. The results showed that forest honey had light amber colour while cultivated honey had extra light amber colour. The pH, viscosity, water content, sugar content, HMF content, and acidity in forest honey were still in compliance with SNI standard, but the ash content was higher than the SNI standard. Cultivated honey had pH, sugar content, and HMF content in the range of SNI standar. However, the viscosity, water content, ash content, and acidity in cultivated honey were not in compliance with SNI standar. Forest honey and cultivated honey had antioxidant capacities about 16.74 mgVCE/g and 16.60 mgVCE/g, respectively. Meanwhile the antioxidant activity were 63.80% and 63.28%, respectively. Forest honey had more physicochemical aspects that were still in compliance with SNI standards compared to cultivated honey. The antioxidant activities of Kerinci honey, both forest honey and cultivated honey, were higher than the results of previous honey studies in other location. Keywords: antioxidant activities; cultivated honey; forest honey; multifloral honey; kerinci honey